Optimization of PEDOT: PSS thin film for organic solar cell application - Abdul Talib, Yuraimy Yakimin (2014)
As a clean and renewable energy source, the development of the organics solar cells is very promising due to the inorganic solar cell inconvenient production process and material shortness. In this work, P3HT: PCBM bulk-heterojunction devices were produced by spin coating organic layers onto ITO coated glass in air, and deposited it with an Au layer as top metal electrode. Inverted devices were fabricated with and without PEDOT:PSS. Then, several attempts have been conducted to improve power conversion efficiency by optimizing different thicknesses of the interlayer between active layer and metal. Power conversion efficiency, short circuit current, open circuit voltage and fill factor were measured on all produced devices. In contrast, the devices with 50 nm thickness of PEDOT: PSS layer showed as better solar cell with 0.0394% efficiency compared to the devices without PEDOT:PSS. As a result, introduction of PEDOT:PSS layer on active layer improves hole collection at the metal / active layer interface.